Hydration and compressive strength of blended cement containing fly ash and limestone as cement replacement - Thongsanitgarn,P. (American Society of Civil Engineers (ASCE), 2015)
© 2014 American Society of Civil Engineers. This study examines the effect of high-calcium fly ash in combination with finely ground limestone as cement replacement on cement's hydration characteristics. Heat released by a hydration reaction was investigated using isothermal calorimetry. X-ray diffraction and thermogravimetric analysis were used to identify hydration products. In this work, fly ash and limestone were used to replace part of Portland cement at 30% by weight in terms of ternary blended cement. All pastes and mortars were cured in water at 23 ± 2 ° C. The compressive strength of mortars were examined for a period of 28 days. The results show that the hydration reaction of cement containing fly ash accelerated when limestone powder was incorporated. Thermogravimetric analysis of the samples hydrated at 28 days show similar hydration products such as ettringite, calcium silicate hydrate, portlandite, and calcite. However, the dehydration of monocarboaluminate was observed in ternary blended cements of Portland, fly ash, and limestone. From X-ray diffraction patterns, the hydration products of ternary blended cements were found to be mostly similar to that of plain Portland cement; however, monocarboaluminate has been detected. The compressive strength at early ages of ternary blended cements was higher than that of fly ash cement, which conforms to the heat of hydration and thermogravimetric results.